A new insight into the degradation of anthocyanins: reversible versus the irreversible chemical processes - Sousa, Diogo (2022)
The kinetics and thermodynamics of the pH-dependent reversible and irreversible processes leading to color fading of pelargonidin-3-O-glucoside, peonidin-3-O-glucoside, malvidin-3-O-glucoside, and cyanidin-3-O-glucoside dyes in aqueous solutions are reported. Following the addition of base to the flavylium cation, the quinoidal bases disappear by three distinct steps: (i) in an acidic medium by a biexponential process, in which the faster step is controlled by the hydration reaction and the slower one by cistrans isomerization; the degradation process occurs essentially from the anionic quinoidal base; (ii) in a basic medium (pH > 9.5), in which the disappearance of the anionic bases is monoexponential, with the rate proportional to the hydroxyl concentration (hydroxyl attack), leading to anionic chalcones (cis and trans) at equilibrium-the slower degradation step occurs from the di- and trianionic chalcones; and (iii) in the pH region circa 7.7 < pH < 9.5, in which hydration and hydroxyl attacks are much slower than anionic quinoidal base degradation (which is the rate-controlling step) and the equilibrium cannot be attained.